Integrating Objective Weighting and Performance Analysis for Solving Green Energy Management Challenges - Lin, Keng-Yu; Chang, Kuei-Hu; Lin, Po-Ting; Chang, Hsiang-Yu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The world is facing an ecological crisis, as carbon emissions from the global construction industry place a significant burden on the environment. Well-designed green energy management (GEM) can mitigate carbon emissions and promote sustainable environmental development. However, assessing green energy involves a complex process of multi-criteria decision-making (MCDM). Traditional approaches cannot accurately account for the objective weight of evaluation criteria, fail to consider the positive and negative ideal solutions of alternatives, and lack an integrated assessment from a multi-dimensional perspective. As a result, the evaluation of green energy remains incomplete. To address these limitations, this study integrates criteria importance through inter-criteria correlation (CRITIC) and the technique for order of preference by similarity to ideal solution (TOPSIS) within a two-dimensional matrix framework to provide managers with decision-making guidance for GEM. A case study on selecting green building insulation materials was conducted to compare the proposed approach with the simple additive weighting (SAW) approach and the TOPSIS approach. The calculation results demonstrate that the proposed approach more accurately evaluates alternative ranking through a visualized framework, offering a more reliable and comprehensive decision-making tool for GEM.